Does hemispheric dominance influence brain lesion distribution in multiple sclerosis?. Issue 6 (June 1995) - Filippi, M; Martino, G; Mammi, S; Campi, A; Comi, G; Grimaldi, L M
Abstract : To evaluate whether hemispheric lesion distribution in multiple sclerosis is related to the uneven interhemispheric localisation of cerebral function, a 10 item self administered questionnaire evaluating hand preference and supratentorial brain MRI was obtained in 23 patients with clinically definite multiple sclerosis. The mean degree of hand preference was +74 (range -86 to +100). The median lesion volumes were 7275 (range 1045-22, 440) mm3 for the left hemisphere and 5385 (range 1010-19, 490) mm3 for the right hemisphere. The degree of hand preference correlated with the index of interhemispheric lesion distribution (P = 0.02). The data suggest that local events, possibly related to specialisation of hemispheric function, might be responsible for the increased vulnerability of the dominant hemisphere to the pathological process of multiple sclerosis.